2019
DOI: 10.3390/biom9090424
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Panax ginseng Berries from Seven Cultivars Using UPLC-QTOF/MS and NMR-Based Metabolic Profiling

Abstract: The commercial use of Panax ginseng berries is increasing as P. ginseng berries are known to contain large amounts of ginsenosides, and many pharmacological activities have been reported for the various ginsenosides. For the proper use of P. ginseng berries, it is necessary to study efficient and accurate quality control and the profiling of the overall composition of each cultivar. Ginseng berry samples from seven cultivars (Eumseung, Chung-buk Province, Republic of Korea) were analyzed using ultra-performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…1 B), but lowest Re among the others. Such finding has been supported by Yoon et al [ 9 ]. Anti-inflammatory activity of Kumpoong and K-1 were identified with the effect of LPS-induced NO production in RAW 264.7 cells.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…1 B), but lowest Re among the others. Such finding has been supported by Yoon et al [ 9 ]. Anti-inflammatory activity of Kumpoong and K-1 were identified with the effect of LPS-induced NO production in RAW 264.7 cells.…”
Section: Resultssupporting
confidence: 76%
“…GBs cultivars such as Chunpoong, Kumpoong, and Yunpoong were categorized according to variant physical representations (i.e., berry’s color and stem) [ 8 ]. Yoon et al [ 9 ] reported that only the Kumpoong (yellow color berry) has the highest ginsenoside Rg1 as compared to other existing cultivars. A new cultivar, K-1 has been reported recently with its superior representation which has excellent root shape and strong disease resistance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yoon et al 28 detected malonyl-ginsenoside Rb1 and malonyl-ginsenoside Rd from seven cultivars of ginseng berry based on UPLC-QTOF/MS. Four malonyl-ginsenosides (malonyl-Re, malonyl-Rb 1 , malonyl-Rd, and malonyl-Rb 2 or malonyl-Rb 3 or malonyl-Rc), all of them are polar ginsenosides, were detected in GPS and GPE in the present study in that the ginseng pulps from which GPS and GPE were achieved were soaked in 100% ethanol immediately after picking.…”
Section: Resultsmentioning
confidence: 99%
“…This is helpful when only one class has a medical application as in the case of Trichilia catigua [ 70 ] or Withania somnifera [ 71 ]. It can also help to distinguish between different cultivars of apples [ 72 ], melons [ 73 ], rice [ 74 ], persimmons [ 75 ], ginseng [ 76 ], almonds [ 77 ] and curtis [ 78 ].…”
Section: Applications Of Hr-mas Nmr In Plant Metabolomicsmentioning
confidence: 99%